2016
DOI: 10.1007/s11367-016-1133-6
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the relevance of building components and life phases for the environmental profile of nearly zero-energy buildings: life cycle assessment of a multifamily building in Italy

Abstract: Purpose: Since the construction sector is a considerable energy consumer and greenhouse gas (GHG) producer, the EU rules strive to build nearly zero-energy buildings, by reducing the operative energy and yearning for on-site energy production. This article underlines the necessity to go beyond the energy evaluations and move towards the environmental assessment in a life cycle perspective, by comparing the impacts due to building materials and energy production devices. Methods: We compared the operational ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 45 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…The second type of carbon accounting that places special emphasis on the product has some limitations in regional carbon emissions accounting. [37]. This reference conducts a statistical study of 70 references related to carbon emissions worldwide [38].…”
Section: Research Contentsmentioning
confidence: 99%
“…The second type of carbon accounting that places special emphasis on the product has some limitations in regional carbon emissions accounting. [37]. This reference conducts a statistical study of 70 references related to carbon emissions worldwide [38].…”
Section: Research Contentsmentioning
confidence: 99%
“…The research proved that as buildings are becoming more efficient and using significantly less operational energy over its life time, embodied energy plays a greater role. (Paleari, Lavagna, & Campioli, 2016) Another typical use for whole building life cycle assessment in research is to compare a baseline building and an improved or upgraded building to demonstrate the percent embodied energy or carbon savings the projected is projected to save in compared to a typical new build. The Athena Sustainable Materials Institute has completed a number of studies like this, such as the UBC Biological Sciences Complex Renew project, which proved that the building avoided the consumption of 4 million liters of water, 24,000 gigajoules of fossil fuels, and 13,000 tonnes of materials by renovating rather than demolishing and building new (Athena Sustainable Materials Institute, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on manufacturing systems of various products (Cascini et al, 2016;Di Lullo et al, 2016;Mahbub et al, 2018;Sproesser et al, 2015;Wong et al, 2016) are abundant. Sustainability assessments of chiller manufacturing and product life cycle, however, have been primarily focused on economic and building energy systems (Collinge et al, 2013;Osman & Ries, 2007;Paleari et al, 2016). A study found that electricity used by the chiller dominates a majority of the GHG associated with the life cycle analysis of chiller (Calm, 1999).…”
Section: Introductionmentioning
confidence: 99%